Numerical Study of an External Flow around a Corrugated Wing using Lattice Boltzmann Method - Singh Balbir; Yidris Noorfaizal; Basri Adi Azriff; Pai Raghuvir; Ahmad Kamarul Arifin (E3S Web of Conferences, 2024)
During the course of recent studies on wings at low Reynold number, it was observed that wing corrugation is often assumed to play an important role as well. However, studies show that corrugation of the wing is intended for structural purposes, and not aerodynamics. Corrugated wings have the advantage of being light and sturdy. Therefore, the main aim of this study is to understand the flow behaviour of the corrugated insect-scale wing; by conducting, a geometric parametric study during a non-oscillatory flight at a particular low Reynolds number and at two different angles of attack. In this computational study, a 3-D section of the corrugated wing along the chord is considered. The lattice Boltzmann method offers an alternative framework compared to the Navier-Stokes simulations. An open-source Parallel Lattice Boltzmann Solver on a high-performance computing platform is used for this computational analysis. The present study shows that the flow-related performance of the corrugated wing in terms of forces and kinetic energy is predominantly governed by the geometric variations that can largely affect the formation of vortices and their mutual interaction. The study reveals that the presence of corrugation does not affect the enhancement of forces and corrugation near the leading edge generally affects the performance due to large flow separation affecting the suction.